Women's movements against collective male violence - Denman, Greg (Kansas State University, 2011)
The intention of this thesis was to understand why and how women organized or participated in peaceful movements aimed at stopping collective, organized male violence in the public sphere. Historical archives were used to examine four social movements – Mothers of Plaza de Mayo, Greenham Common Peace Camp, Committee of Soldiers’ Mothers of Russia, and the Antimafia Movement – that attempted to end violence from male organizations. The findings from this thesis discovered that through the process of framing, which was permitted by increased power obtained in society through the workforce, women took a peaceful, self-invested, but overall altruistic, role in social movements.
Keywords: Movements; Sociology (0626)